Culturally sensitive active ageing seen through the lens of the welfare theory of health: assistant nurses’ views - Johansson, Carl; Gustafsson, Lena-Karin; Lindberg, Daniel; Asztalos Morell, Ildikó (Frontiers in Psychology, 2023)
Assistant nurses caring for older adults with immigrant backgrounds are on the front lines of a practical, theoretical, and policy battlefield. They need to implement culturally sensitive care provision while not overstating the importance of culture, thereby, contributing to a negative picture of older immigrants as especially problematic. One proposed way to strike such a balance is the welfare theory of health (WTH). In this article, we let assistant nurses apply the WTH to a series of questions in four different vignettes representing the life stories of older persons who characterize typical dilemmas described by the theory. The results show that, through the lens of the WTH, assistant nurses looked for individual care preferences rather than stereotypical ideas about cultural characteristics. Further, the assistant nurses expressed a desire to get to know the persons more deeply to better interpret and understand their individual preferences. Thus, the theoretical framework is useful not only for exposing vulnerabilities to which some older adults with immigrant backgrounds may be exposed, but also for finding ways to mitigate the vulnerability by illuminating vital life goals and using them as a framework to organize care. This approach allows for mitigating the gap between the vital life goals and available resources to achieve a holistic state of health.